Searching for an Optimal Model for the Renewal of the Constitutional Court to Avoid a Constitutional Crisis: Dream or Reality?* - Jolita Miliuvienė (Law: Journal of the University of Latvia)
The failed renewal of the Constitutional Court in Lithuania was not the first in Europe, and will not be the last. The appointment of constitutional judges, usually undertaken with the involvement of the political institutions, became a very sensitive issue closely linked to their independence. After a sequence of unsuccessful attempts to renew the composition of constitutional courts, some states fall into a deep democratic backsliding, while some take the initiative to reform the existing appointment procedure, seeking to prevent the politicisation of constitutional control institutions. A universal and standardised one-size-fits-all model does not exist, as each particular national context must be considered. However, certain lessons are to be learned and certain pitfalls to be avoided. Constitutional courts must correspond to the criteria of the tribunal established by law, as disclosed in international jurisprudence. For this purpose, the proper law is needed. This article analyses the advantages and shortcomings of some elements of the proposed and partly realised Slovak reform on the appointment of constitutional judges that Lithuania and other states could benefit from. This allows for the conclusion that the explicit criterion of professional reputation might prevent arbitrary nominations and ensure that the best judge for the court and the society would be appointed. Contrary to most convictions, a larger majority in the Parliament is not necessary to keep this procedure in line with the principle of the rule of law. The only requirement is that the law must be clear, unambiguous and provide for the steps to be taken if the rotation fails.